Intestinal parasites in dogs and cats with owners of Barranquilla, Colombia - Sarmiento-Rubiano, Luz Adriana (2018)
The aim of this study was to evaluate the intestinal parasitism in dogs and cats with owners of the city of Barranquilla. A retrospective descriptive study was carried out, which included the reports of coprological analyses made in a veterinary clinical laboratory during the years 2014 and 2015 to 925 dogs and 45 cats from 26 veterinary centres located in the city. Results showed that 73.3% of dogs and 62.2% of cats had some type of intestinal parasites, without significant difference between species. The most frequent helminths were Toxocara sp (12.4 and 8.9% in dogs and cats, respectively), followed by Ancylostoma sp (3.4 and 4.4% in dogs and cats, respectively). The most frequent protozoa were Entamoeba sp, Isospora sp and Giardia sp in dogs and the last two in cats. The high frequency of intestinal parasites of zoonotic transmission found in dogs and cats showed the need to establish corrective and preventive measures for their control based on public health.